Genetic Mutations in Young Nonsmoking Patients With Oral Cavity Cancer: A Systematic Review. Issue 4 (November 2020) - Bahethi, Rohini R.; Stepan, Katelyn O.; Pinotti, Rachel; Li, Ryan; Agrawal, Nishant; Puram, Sidharth V.; Miles, Brett A.; Barber, Brittany
Objective: This investigation aims to review the known genetic mutations associated with oral cavity squamous cell carcinoma (OCSCC) in young adults with limited environmental risk factors (YLERs). Data Sources: A comprehensive search strategy was designed to identify studies in MEDLINE (Ovid), Embase (Ovid), and Scopus from database inception to May 2017 that included adults ≤50 years of age with OCSCC and minimal tobacco use history (≤10 pack-years) who had their tumors genetically sequenced or mutational profiles analyzed. Review Methods: Identified articles were screened by 2 reviewers. Quality of evidence was graded by the MINORS criteria for case-control studies; other studies were graded by assigning a level of evidence for gene mutation literature. Results: Thirteen studies met our inclusion criteria, and 130 patients met our criteria for age and tobacco history. TP53 was the most commonly evaluated gene (10 of 13 studies) and the most frequently observed mutation. One study reported that nonsmokers had significantly fewer TP53 mutations, while 9 studies found no difference in the prevalence of TP53 mutations. No other mutations were found specific to this cohort. Conclusions: TP53 mutations may occur at a similar rate in YLERs with OCSCC as compared with older patients or those with risk factors. However, few studies have aimed to characterize the genetic landscape of oral cavity tumors in this population, often with small sample sizes. Future studies are needed to explore unidentified genetic alterations leading to tumor susceptibility or alternative mechanisms of carcinogenesis.